Public Private Partnerships: Strategic Assets and Managerial Models - Paola Olimpia Achard; Antonina Di Berardino (International Telecommunications Society (ITS), 2018)
Most of existing contributions on Public-Private Partnership (PPP) refer to a traditional and financial perspective, or rather to an unbalanced strategic relationship between the public and the private actors. Starting from a PPP traditional definition, the objective of the paper is to analyze: a) the strategic and managerial challenges and changes in the PPP concept, highlighting the institutional lens of investigation; b) the critical role of shared PPP strategies for the long-term sustainability; c) the value generated and shared for the societal wealth and wellbeing. The paper is divided into three sub-sections. The first one is aimed at shortly analyzing the institutional framework and the sectorial trend and distribution of PPPs. The second one highlights the strategic assets, the managerial approach to PPPs, and the relevance of the multi-stakeholder engagement. The followed approach consists in the multidimensionality analysis of the PPP role and models, according to the necessity to manage uncertainty and create shared value for the direct stakeholders and the indirect ones. The last section introduces the ZTE incidence case, describing the 5G project of L'Aquila (Abruzzi).
Keywords: 330; public-private partnership; PPP; strategic and managerial approaches; shared value; ZTE; L'Aquila